Post-Chornobyl Areas as a Tourist Destination - Igor KAVETSKYY (Communications of International Proceedings, 2021)
The aim of the study is to present the attractiveness of the post-Chornobyl area as a tourist destination in the context of the basic motives for taking a trip to this zone. It includes a short description of areas referred to as post-Chornobyl areas, covering a total of over 600,000 hectares within Ukraine and Belarus, paying attention to their different formal and legal status regulating the possibilities of tourist use. It also contains information concerning the development of tourist traffic in the studied zone, taking into consideration both organized trips (study visits) as well as illegal trips (Chornobyl stalking). The exponential nature of the dynamics concerning the number of visitors to the post-Chornobyl areas in the period 2000-2020 has been emphasized. Furthermore, the results of a pilot survey aimed at identifying the tourist motivation of people undertaking trips to the Chornobyl zone have been presented. It has been found that the main motive for tourists to undertake Chornobyl expeditions consists in cognitive interest resulting from the unusual character of the specific locations, combined with inborn human curiosity and natural attraction to adventure. The important role of media-related factors, related mainly to computer games and the film industry, has also been indicated.
Keywords: post-Chornobyl areas; tourist motivation; study visits; Chornobyl stalking